Hubungan Antara Kepatuhan Membatasi Cairan Minum dengan Motivasi dan Kualitas Hidup Pasien Hemodialisis di Rumah Sakit Santa Theresia Jambi - Paulus Daryanto; Mardiana; Iswadi; Aguspairi; Sri Mulyati (Nightingale: Journal of Nursing, 2026)
Chronic kidney disease (CKD) is a growing global health problem that affects patients’ quality of life. Patients with end-stage CKD undergoing hemodialysis require strong adherence to fluid restriction, while motivation also plays an important role in improving quality of life. This study aimed to analyze the relationship between fluid restriction adherence, motivation, and quality of life among hemodialysis patients at Theresia Hospital Jambi. This quantitative study used a cross-sectional design involving 33 respondents selected through purposive sampling. Data were collected using questionnaires and analyzed with the Chi-Square test. The findings showed that most respondents had high adherence (69.7%), high motivation (72.7%), and good quality of life (66.7%). There was a significant relationship between fluid restriction adherence and quality of life (p = 0.033), as well as a highly significant relationship between motivation and quality of life (p = 0.000). In conclusion, higher adherence and motivation are associated with better quality of life in hemodialysis patients. Improving patient education and psychological support is important to enhance adherence and overall quality of life.